Edukasi Tentang Pelatihan Androgogik Terhadap Peningkatan Public Speaking Pada Mahasiswa - Ariawati Susiandari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The ability to speak in public is commonly referred to as public speaking, which is part of non-formal education, specifically skills education. With the skills one possesses, they can have better self-confidence. Public speaking plays a significant role in interactions between individuals. This service activity, which is educational training, is carried out with the aim of providing development and expertise that benefits both the individual and the company or organization. Along with the development of times, the need for soft skills training such as public speaking has become a priority for many people. In fact, many parents also prepare their children to have good public speaking skills from an early age. Public speaking training is not only important for personal development but also plays a significant role in supporting success in various fields, such as in the workplace, education, and social activities. Therefore, it is essential for each individual to have good public speaking skills to face various challenges in communication and interaction with others. This training provides an understanding of effective speaking techniques, ways to overcome nervousness, and enhances the ability to communicate clearly and confidently.